REKONSTRUKSI PALEOBATIMETRI DAN PENENTUAN BATAS PENGENDAPAN BERDASARKAN KELIMPAHAN FORAMINIFERA: STUDI KASUS PADA SEDIMEN INTI SO189/2-04KL DI CEKUNGAN BENGKULU - Taufan Wiguna; Sri Ardhyastuti (Laboratory for Marine Survey Technology, 2021)
[Paleobathymetry Reconstruction and Depositional Boundary Based on Foraminifera Abundance: a Case Study on So189/2-04kl Sediment Core in Bengkulu Basin] Paleobathymetry reconstruction and deposition boundary determination in an oil and gas industry has been used widely to study geological history on a basin. Those approaches could be done by microfossil proxy, including use of foraminifera. Using the foraminifera abundance and P/B ratio, this study tries to reconstruct paleobathymetry and determine depositional boundary on sediment core SO189/2-04KL 600-900 cmbsf in Bengkulu Basin. As a result, both parameters show paleobathymetry changes between outer neritic and inner bathyal. Inner bathyal only appear on interval 780-785 cmbsf. Maximum flooding surface appear on depth 640, 736.5, and 825 cmbsf while transgressive surface appears on depth 701, 765, and 890 cmbsf. Keywords: paleobathymetry, maximum flooding surface transgressive surface, P/B ratio, foraminifera abundance